Equipment diagnostic audit model for energy optimisation of centralisation air conditioning system - Lei, Fuying. (2008)
This project aims to develop an equipment diagnostic model to identify the most influential factors affecting the energy efficiency of typical centralized air conditioning systems (CACS).